Making meaning in a modern world: place and identity in Leadville, Colorado - Hawk, Jennifer, author; Fiege, Mark, advisor; Ore, Janet, advisor; Calderazzo, John, committee member (Colorado State University. Libraries, 2010)
Leadville, Colorado is one of many former mining towns significant to not only the state of Colorado, but also to the history of the West as a whole. Part of the larger history of the extractive industries on which the Western United States was founded, mining towns like Leadville provide a postindustrial landscape through which to study the ways in which individuals and communities rely on their history and memory to maintain a stable identity in a modem world that no longer accommodates the kind of economic structure that they most strongly identify with. This thesis consists of three parts, two of which offer a more traditional historical study of the ways in which Leadville residents use their past to mitigate the realities of life in the modem world. The third portion, a non-fiction essay, reflects on my own experiences with both Leadville and with the nature of modem life.
Covers not scanned.
Keywords: Historic sites -- Colorado -- Leadville; Group identity -- Colorado -- Leadville